Happy people are annoying - Peck, Josh, 1986- (HarperOne, an imprint of HarperCollinsPublishers, 2022)
A wonderfully candid memoir from one of the most recognizable faces of a generation, actor, writer, Youtuber, and television superstar, Josh Peck. In his warm and inspiring book, Josh reflects on the many stumbles and silver linings of his life and traces a zigzagging path to redemption. Written with such impressive detail and aching honesty, Happy People are Annoying is full of surprising life lessons for anyone seeking to accept their past and make peace with the complicated face in the mirror.